A new Canadian health care initiative in Tanzania. - Finlay, J F (1995)
One of the main conclusions of the World Bank's World Development Report 1993--Investing in Health was that equitable access to a package of essential clinical and public health services could significantly reduce the overall burden of disease in low-income countries. The report argued that more rational and effective decisions with regard to the allocation of limited resources could be made on the basis of burden-of-disease and cost-effectiveness analyses. In collaboration with the Canadian International Development Agency and several other organizations, the International Development Research Centre has developed the Essential Health Interventions Project to test the feasibility of this approach in a few districts in Tanzania. Outcome assessment wil focus on improved planning at the district level and on changes to the health status of the study population.